2013
DOI: 10.12820/rbafs.v.18n4p453
|View full text |Cite
|
Sign up to set email alerts
|

Efeito do treinamento aquático no perfil lipídico e na hipertrofia ventricular esquerda de camundongos hiperlipidêmicos

Abstract: ResumoO objetivo do presente estudo foi analisar os efeitos do treinamento aquático (TA) no perfil lipídico e nas estruturas ventriculares esquerdas de camundongos hiperlipidêmicos. Foram utilizados 28 camundongos LDLr-/-, machos, divididos aleatoriamente em 4 grupos: sedentários alimentados com ração padrão (C); treinados alimentados com ração padrão (C+TRE), sedentários alimentados com ração hiperlipídica (HL) e treinados alimentados com ração hiperlipídica (HL+TRE). Os animais dos grupos treinados praticara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Previous studies conducted in our laboratory have demonstrated that LDLR-/-mice fed high-fat diets developed severe mixed hyperlipidemia followed by a decrease in the serum levels of HDL and left ventricular hypertrophy (4,(15)(16)(17), which involves CD40L signaling (3). Furthermore, they presented lipid peroxidation and protein oxidation associated with insulin resistance with hyperinsulinemia (4,15) and increased serum levels of CRP ( 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies conducted in our laboratory have demonstrated that LDLR-/-mice fed high-fat diets developed severe mixed hyperlipidemia followed by a decrease in the serum levels of HDL and left ventricular hypertrophy (4,(15)(16)(17), which involves CD40L signaling (3). Furthermore, they presented lipid peroxidation and protein oxidation associated with insulin resistance with hyperinsulinemia (4,15) and increased serum levels of CRP ( 4).…”
Section: Discussionmentioning
confidence: 99%